Potential of Olive Oil Extract (Olea europaea) For Affecting Lipid Profile, Lipid Oxidative and Fatty Liver on Hiperlipemic Rats (Rattus norvegicus) - Hanifwati, Annisa; Marhendra, Agung Pramana Warih; Aulanni'am, Aulanni'am (Graduate School, Universitas Brawijaya, 2019)
Olive oil (Olea europaea) contains 55 to 83% oleic acid which is a single chain unsaturated fatty acid or mono-unsaturated fatty acid (MUFA), and 2% phenolic components in the form of hydroxytyrosol and tyrosol. This study aims to determine the potential of olive oil extract (Olea europaea) in reducing cholesterol and malondialdehyde levels, along with inhibiting fatty liver development in hiperlipemic rats. Sixteen rats were divided into four groups, the first group was healthy control group, the second group was positive control group, received a high-fat diet containing 100 mg of cholesterol powder, 25 mg of cholic acid powder and 1 mL of quail egg yolk for 28 days. Third and fourth treatment groups were received for 28 days, plus 0.828 g (1 mL) and 1.656 g (2 mL) of olive oil extract daily for 14 days, respectively. The measurement of total cholesterol used cholesterol test strips based on oxidation enzyme reaction cholesterol esterase and cholesterol oxidase that produce hydrogen peroxidation, then analyzed with biosensor refractophotometry. Measurement of malondialdehyde used thiobarbituric acid (TBA) test. Histological observation of fatty liver was assessed using a NAS (Non-alcoholic fatty liver disease score). The results showed that 1.656 g (2 mL) of olive oil extract per day decreased total cholesterol level up to 44.41 %, malondialdehyde level up to 61.75%, and NAS score up to 50%, compared with positive control. It was concluded that olive oil extract was decreasing total cholesterol level, as an anti-oxidant and prevent fatty liver development.Keywords: fatty liver, hyperlipidemia, malondialdehyde, Olea europaea.